Jordanian Customer's Intention to Use Online Food Delivery Services - Ibrahim F M Alajaleen; Chang, Chia-Hua (Journal of Business Transformation and Strategy, 2026)
Abstract: This study investigates the factors that shape Jordanian consumers’ intention to adopt online food delivery services (OFDS). Drawing upon the Technology Acceptance Model (TAM) and incorporating individual innovativeness, trust, and perceived risk, the research examines how these variables influence perceptions, attitudes, and behavioral intentions. Data were collected from 344 respondents and analyzed using structural equation modeling. The findings confirm that perceived ease of use and perceived usefulness are the strongest predictors of positive attitudes toward OFDS, which in turn strongly drive behavioral intention. Individual innovativeness enhances perceptions of usefulness and ease of use, although it does not directly strengthen attitudes or trust. Interestingly, perceived risk and trust, which are often central in other adoption contexts, were not decisive factors in the Jordanian setting. Instead, consumers focused primarily on the convenience and benefits of the service, reflecting cultural differences in how adoption decisions are formed. The study contributes to theory by extending TAM with personality traits and contextual variables, highlighting the moderating influence of culture. Practically, it offers guidance for service providers by underscoring the importance of simple, user-friendly design and benefit-focused communication. The paper concludes by discussing limitations related to sampling and scope and by proposing future research directions that incorporate broader service and cultural dimensions